Effects of halothane on glucose metabolism after injury in the rat. - Heath, D; Frayn, K; Rose, J (1978)
The effects of halothane anaesthesia on glucose metabolism have been investigated in rats after a non-lethal scald injury. Anaesthesia was induced about 70 min after injury. Glucose metabolism was studied at two stages: during and shortly after induction, and about 2 h after induction. Comparisons were made with conscious rats at the corresponding times after injury. All rats were in an ambient temperature of 30 degrees C. During and shortly after the induction of anaesthesia, halothane caused a rapid increase in plasma glucose concentration, which by 30 min had begun to return to the values in injured controls; thus glucose production and utilization were increased. Insulin concentrations were increased also. However, after 2 h exposure halothane had decreased glucose production and utilization, as determined with [5-3H]- and [U-14C]-glucose, increased plasma concentrations of insulin and decreased liver concentrations of glycogen, that is it had exacerbated well-known effects of injury in the rat, including insulin resistance. Hyperglycaemia was not increased.